Effective teaching modifies medical student attitudes toward pain symptoms - Schreiner, Ute; Haefner, A.; Gologan, Renata; Obertacke, Udo (European journal of trauma and emergency surgery, 2011)
Recent studies have raised the question of whether last year medical students and first year residents show an adequate attitude toward their patient’s pain as reflected by prescribed pain medication. Underuse of analgetics could be demonstrated in several studies even after a correct diagnosis of pain was made and has led to the term “oligoanalgesia.” Our study was aimed at evaluating the potential of improving student attitudes toward pain by changing the curriculum during the last year of medical education.
Gesehen am 26.10.2022